Effects of Dietary Fish Meal Replacement with Alternative Protein Ingredients and Their Combinations on Growth Performance, Feed Utilization, Fillet Composition, and Biochemical Parameters of Red Seabream (Pagrus major) - Buddhi E. Gunathilaka; Seong-Mok Jeong; Min-Uk Cho; Kang-Woong Kim; Sang-Woo Hur; Seunghan Lee; Sang-Guan You; Sang-Min Lee (Aquaculture Nutrition, 2023)
The experiment was conducted to evaluate alternative protein ingredients in a low-fish meal (FM) diet for red seabream (Pagrus major). Twelve experimental diets were formulated. Control diet (CON) was designed to contain 60% FM. Other experimental diets were formulated by replacing 50% of FM from the CON with soy protein concentrate (SPC), corn gluten (CG), meat meal (MM), and/or chicken byproduct meal (CBM). Four diets were designed including one of SPC, CG, MM, or CBM as FM replacer and designated as SPC, CG, MM, and CBM. Six other diets were formulated by adding two ingredients as SPC and CG, SPC and MM, SPC and CBM, CG and MM, CG and CBM, or MM and CBM, and designated as SCG, SMM, SCM, CMM, CCM, and MCM, respectively. The 12th diet (MIX) was formulated by including SPC, CGM, MM, and CBM. Triplicate fish groups (50.2 ± 0.1 g) were hand-fed for 12 weeks. Weight gain (WG) of fish was significantly improved by MM and MCM diets compared to CG, SCG, CMM, and CCM diets. WG of CON, SPC, CM, SMM, SCM, and MIX groups were comparable with MM and MCM groups. The lowest WG was observed in CG and CMM groups. Feed efficiency (FE) was significantly higher in MM group compared to SPC, CG, SGC, and CMC groups. FE of MCM group was significantly higher than CG and SCG groups. Fillet linolenic acid (C18:2n–6) level in CG group was significantly higher than CON, MM, CM, SCM, CCM, and MCM groups. Serum lysozyme activity was significantly higher in MCM and MIX groups. Therefore, a high level of dietary CG reduces the growth performance and feed utilization of red seabream. A mixture of MM and CBM seems to be more efficient in replacing FM from red seabream diet.